Environmental regulations and eco-innovation as catalysts for green agricultural practices: insights from Pakistan–China agricultural cooperation - Ali Raza; Lu Hongliang; Zhu Yue; Tingyu Yang; Nian Wei (Agricultural and Food Economics)
Abstract This paper explores the adoption of green production technology within the framework of Pakistan–China agricultural cooperation under the China–Pakistan Economic Corridor. The research focus is on how farmers’ green values (FGVs) and energy use reduction (EUR) affect the adoption of green production technology (AGPT), mediating through green production willingness (GPW), with environmental regulation and eco-innovation as moderators. The study conducts an analysis based on the use of structural equation modelling (SEM) and random forest regressor (RFR), wherein the drivers of sustainable agricultural practice are discussed. For this primary quantitative study, data were gathered via the survey method from 366 rural farmers, and SEM was performed to test hypotheses. SmartPLS software was used for this purpose. The results obtained show that both FGV and EUR have significant impacts on AGPT. However, ER insignificantly influences GPW. The mediation of GPW was significant in the association between FGV and AGPT (p < 0.05). However, it was insignificant in the relationship between EUR and AGPT (p > 0.05). The sequential mediation of GPW and AGPT was also found to be insignificant (p > 0.05), whereas AGPT has a significant impact on green supply chain performance (GSP). The moderation of environmental regulation was also insignificant (p > 0.05), while the moderation of eco-innovation was significant (p < 0.05). The RFR model also supported the impact of FGV and EUR on GSP. This insight indicates the critical role of environmental regulations, technological advancements, and the enhancement of supply chain performance through AGPT. This study fills an important literature gap regarding cross-national cooperation for sustainable agriculture in developing countries by integrating behavioural, regulatory, and technological perspectives.